Quantification of therapeutic effect of yoga in children with autism spectrum disorder - Soccalingam Artchoudane; Meena Ramanathan; Ananda Balayogi Bhavanani; Muruganandam Partheeban; Lakshmi Jatiya; Anandaraj Lokeshmaran (Wolters Kluwer Medknow Publications, 2023)
Aim: The aim is to evaluate the quantification of the therapeutic effect of yoga in children with autism spectrum disorder (ASD). Design: The study design involves randomized controlled trial. Setting: The study was conducted in Satya Special School, Puducherry. Patients: Data on 18 children with ASD were collected after 6 months of yoga therapy intervention. Methods: Collection of the data necessary to develop a therapeutic effect scoring system in yoga for autism spectrum disorder (TESS-YFA) which is the average of the first three times of practice for each yoga technique given in the yoga therapy protocol after completion of yoga intervention. Results are presented as mean ± standard deviation and the data were normally distributed. Measurements and Results: The overall mean therapeutic effect scoring system (TESS) (5)-YFA was significantly lower than the mean TESS (4)-YFA. Thus, both systems showed highly significant mean differences (p < 0.001). TESS (4)-YFA was 25% higher than TESS (5)-YFA with the same coefficient of variation (34.3%). The relationship between the two systems was TESS (4)-YFA = 19.93 + 4.98 TESS (5)-YFA. Conclusion: TESS (4)-YFA was validated and showed a higher therapeutic effect in the scoring system with the same coefficient of variation. Thus, the results indicate that TESS (4)-YFA can replace TESS (5)-YFA for the measurement of the therapeutic effect of yoga in children with ASD.